The Effect Of Home Visits By Nurses On Increasing Compliance With Taking Medication In Pulmonary TB Patients - Rony Alexander Latumenasse; Arriani Indrastuti; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Pulmonary tuberculosis (TB) is a chronic infectious disease that requires long-term treatment and high adherence to achieve recovery. Non-adherence to medication is a major cause of treatment failure and the emergence of drug resistance. Home visits by nurses are a community nursing intervention aimed at improving patient adherence through education, monitoring, and psychosocial support. This study aimed to determine the effect of home visits by nurses on medication adherence in pulmonary TB patients. The study used a quasi -experimental design with a one-way approach. group Pretest - posttest. The sample consisted of 30 pulmonary TB patients selected using a purposive sampling technique. Medication adherence was measured using a compliance questionnaire. Data were analyzed using the Wilcoxon test. Signed Rank Test. The results of the study showed an increase in medication adherence after home visits with a p value = 0.000 (<0.05). The conclusion of this study is that home visits by nurses have a significant effect on increasing adherence to taking medication in pulmonary TB patients.